An optical detection method for analyzing the cellular response to paclitaxel at the single cell level. Issue 18 (26th April 2016) - Wang, Yijia; Zhang, Yuquan; Zhang, Shiwu; Zhao, Zhenying; Min, Changjun; Liu, Jun; Yuan, X.-C.
Abstract : The detection of cellular responses to drugs is important for biomedical research, but there is a lack of convenient label-free methods to analyze responses at the single cell level. Abstract : The detection of cellular responses to drugs is important for biomedical research, but there is a lack of convenient label-free methods to analyze responses at the single cell level. The refractive index is a typical biophysical parameter reflecting the cell status. An optical tweezer system was established to measure the trapping efficiency, which relates to the refractive index. The response of two cancer cell lines and their paclitaxel resistant counterparts were measured using optical tweezers. Cyclin B1 expression, polymerized tubulin and caspase-3 activation were measured, compared and associated with the trapping efficiency. The results show that the trapping efficiency declined sharply when caspase-3 was activated. These results suggest that optical tweezers can be used as an auxiliary method to analyze cellular responses to anti-tumor drugs.